2010
DOI: 10.26719/2010.16.8.886
|View full text |Cite
|
Sign up to set email alerts
|

Impact of using essential drug list: analysis of drug use indicators in Gaza Strip

Abstract: A descriptive cross-sectional study evaluated the compliance of physicians with the Palestinian essential drug list (EDL) in all the government primary care clinics in the Gaza Strip. While 67.4% reported currently using the EDL 51.2% of these physicians reported problems in using it. The mean number of drugs per prescription was 1.92, the percentage of drugs prescribed from the EDL was 97.9% but the percentage of drugs prescribed by generic name was only 5.5%. A copy of the EDL was available in 28.3% of clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 2 publications
3
21
0
Order By: Relevance
“…This is similar to studies in Bahrain (99.8%) [21] and Gaza Strip (97.9%) [19]. Generally in other developing countries values higher than 80% have been reported [15][16][17][18].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This is similar to studies in Bahrain (99.8%) [21] and Gaza Strip (97.9%) [19]. Generally in other developing countries values higher than 80% have been reported [15][16][17][18].…”
Section: Discussionsupporting
confidence: 78%
“…Although this value was within the acceptable limit proposed in this study (≤ 3 drugs prescribed per patient encounter) and none of the PHCCs were above the cutoff value, data from some other developing countries reported a lower average number of Table 1 drugs per encounter, ranging from 1.3-2.2 [15][16][17][18]. In a study conducted in Gaza Strip, the mean number of drugs per prescription was 1.92 [19]. However, in a study carried out in 50 PHCCs across 5 governorates of Kuwait, the mean number of drugs prescribed per prescription was 2.9 [20] and in 4 PHCCs of Bahrain, the average number of drugs per encounter was 2.6 [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was lower than that in Gaza Strip, where the availability of key drugs was 82.6% [18]. A shortage of supplies of essential drugs that treat common health problems is harmful to the health status of patients [10].…”
Section: Facility Indicatorsmentioning
confidence: 99%
“…In Yemen, a study reported that the EDL was only available in 78.9% of health facilities at different levels [6]. However, in Gaza Strip a copy of the EDL was only available in 28.3% of clinics [18]. WHO recommends adherence of physicians to the drug listed in the EDL/formulary when prescribing medications in order to ensure effective health care for all [9].…”
Section: Facility Indicatorsmentioning
confidence: 99%